Landscaping for Wildlife in the Pacific Northwest - Link, Russell (Book collections on Project MUSE., 1999)
"Whether you are planting a yard from scratch or modifying an existing area, Landscaping for Wildlife in the Pacific Northwest will help you select, arrange, and maintain plants and other landscape elements that fulfill wildlife needs. Homeowners, property owners, professional wildlife managers, landscape architects, and garden designers will all find it invaluable."--Jacket.